THE ANALYSIS STUDY OF VISUAL IMPAIRMENT AND BLINDNESS DUE TO MACULAR DISEASES: A COMPREHENSIVE SYSTEMATIC REVIEW - Izumi, Tamara; Afifah, (Journal of Advanced Research in Medical and Health Science (ISSN 2208-2425), 2024)
Background: DME and AMD are major causes of blindness, affecting the macula and central vision. AMD accounts for 8.7 of global blindness cases. Understanding AMD beyond the retina can provide insights into its pathophysiology, consequences, therapy, and clinical course. Anti-VEGF agents have shown promise in treating AMD, but a definitive treatment remains unidentified. Methods: Following PRISMA 2020 guidelines, this systematic review concentrated on full-text English literature published between 2014 and 2024. Editorials and review articles that appeared in the same journal as the submission were not accepted without a DOI. A number of websites, including ScienceDirect, PubMed, and SagePub, were utilized to gather the literature. Result: The study looked at more than 400 publications using reputable sources including Science Direct, SagePub, and PubMed. After it was decided that eight publications needed greater investigation, a more extensive review of the entire literature was carried out. Conclusion: BCVA is crucial in the treatment of AMD and DME, with targeting VEGF being an effective approach. However, their effectiveness in other forms of AMD is less convincing. Chronic inflammation is a key factor in retinal diseases, including AMD. DME treatment requires a multidisciplinary approach, with anti-VEGF agents being the first-line treatment.